Searching for a Balance between Work and Leisure from the Perspective of Generational Change in Lithuanian Society - Savicka, Aida (Socialinė teorija, empirija, politika ir praktika, 2023)
Work and leisure are interlinked and mutually determining spheres of human life, both of which are socially constructed concepts that depend on a variety of cultural, social and economic factors. In contemporary society, the balance between work and leisure is particularly relevant in the light of various social, economic and technological changes, such as the intensification of work, the constant accessibility of workers to smart communication devices, the blurring of the boundaries between professional and private time, the introduction of flexible forms of work organisation, etc. The pursuit of work-life balance is therefore even becoming a kind of cultural value imperative aimed at ensuring individual and societal well-being. Using empirical data from the European Values Survey spanning almost three decades (1990-2017), this paper analyses the dynamics of value orientations related to work and leisure in Lithuania, in order to see how the importance of these areas of life and the perception of their relationship to each other is changing in different groups of the population, and how this is related to the change of generations. Data were analysed using descriptive statistics, factor analysis, nonparametric covariance analysis and multiple group comparison test and revealed significant differences in value attitudes related to work and leisure and their interrelationship in different social generations in Lithuania, suggesting that, while the importance of work itself has remained essentially unchanged, we are witnessing a profound cultural change, manifested as a broadening of the spectrum of expectations related to work and a search for a better work-life balance.